2018
DOI: 10.1213/ane.0000000000003482
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Continuous Noninvasive Blood Pressure Monitoring During Noncardiac Surgery

Abstract: BACKGROUND:Intraoperative hypotension is associated with postoperative mortality. Early detection of hypotension by continuous hemodynamic monitoring might prompt timely therapy, thereby reducing intraoperative hypotension. We tested the hypothesis that continuous noninvasive blood pressure monitoring reduces intraoperative hypotension.METHODS:Patients ≥45 years old with American Society of Anesthesiologists physical status III or IV having moderate-to-high-risk noncardiac surgery with general anesthesia were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 18 publications
5
88
1
1
Order By: Relevance
“…In addition, continuous invasive BP monitoring detects twice as much intraoperative hypotension than intermittent non-invasive measurements using oscillometry and triggers vasopressor therapy in adults having non-cardiac surgery [9]. Continuous non-invasive BP monitoring-compared to intermittent non-invasive measurements using oscillometry-also reduces the amount of intraoperative hypotension [10,11]. However, validation studies comparing continuous noninvasive BP measurements to continuous invasive BP measurements using an arterial catheter revealed contradictory results regarding the interchangeability of the methods [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, continuous invasive BP monitoring detects twice as much intraoperative hypotension than intermittent non-invasive measurements using oscillometry and triggers vasopressor therapy in adults having non-cardiac surgery [9]. Continuous non-invasive BP monitoring-compared to intermittent non-invasive measurements using oscillometry-also reduces the amount of intraoperative hypotension [10,11]. However, validation studies comparing continuous noninvasive BP measurements to continuous invasive BP measurements using an arterial catheter revealed contradictory results regarding the interchangeability of the methods [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of these systems is the absence of remote data on physical parameters such as heart or respiratory rates, oxygen saturation and blood pressure. This appears to be a major limitation although several studies have demonstrated that remote monitoring of physiological parameters can signi cantly reduce morbidity or mortality over the perioperative period [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…In this small exploratory study, we did not look at post-procedural morbidity. However, it is now well established that intraoperative arterial hypotension is an independent predictor of increased one-year mortality, especially in patients with pre-existing comorbidities [17][18][19]. We can only suspect that excess hypotension might be deleterious in patients with cardiovascular comorbidities undergoing gastro-intestinal endoscopy, but further investigation is warranted to explore this hypothesis.…”
Section: Plos Onementioning
confidence: 99%